Study of the Financial Feasibility of a Dairy Farming Business after the FMD Outbreak in Kampung Susu Lawu, Plaosan District, Magetan Regency - Setiawan Dwi Ing Marantha; Sutrisno Hadi Purnomo; Ayu Intan Sari (Universitas Sebelas Maret, 2024)
Objective: An outbreak of Foot-and-Mouth Disease (FMD) in Indonesia targeted ruminants, notably impacting dairy cows and precipitating a significant downturn in milk production during the year 2022. This research aimed to determine the financial feasibility and break-even point of post-FMD dairy farming within the Kampung Susu Lawu livestock group in Plaosan District, Magetan Regency.Methods: Employing a quantitative descriptive method, this study utilized survey techniques involving 50 dairy farmers affiliated with the Livestock Group of Kampung Susu Lawu. The data analysis encompassed investment analysis, including the Benefit Cost Ratio (BCR), Net Present Value (NPV), Internal Rate of Return (IRR), Pay Back Period of Credit (PPC), and Break-Even Point (BEP).Results: The findings revealed a BCR value of 1.49, NPV amounting to IDR 38,888,178.00, IRR at 26.36%, PPC of 3.46 years, BEP pegged at IDR 33,043,062.00/year, and BEP based on the unit set at 7,396 liters of milk/year. Financial analysis indicated a positive NPV, a BCR exceeding 1, an IRR surpassing prevailing bank interest rates, and a PPC duration of 3.46 years, collectively affirming the financial feasibility of the dairy farming business.Conclusions: This investigation shows that the post-FMD smallholder dairy business is economically feasible. Farmers stand to accrue benefits by surpassing the production threshold of 7,396 liters of milk/year or by maintaining a herd of productive dairy cows numbering more than three.